Building Children's Awareness with Local Knowledge-Based Mangrove Literacy Models in Coastal Areas - Harto Wicaksono; Atika Wijaya; Asma Luthfi; Fajar Fajar (Komunitas, 2023)
Degradation of coastal environment that occurs in parts of Indonesia's coastal areas is generally caused by erosion, climate change, development, and loss of mangrove forests. This degradation also has an impact on the reduction of the land area inhabited by the community. Bedono Village in Sayung District, Demak Regency, Central Java is one of the areas with the worst conditions, where a third of its area was lost due to tidal floods. One alternative solution that can be done is to restore the function of mangroves in a sustainable manner which is carried out on a local basis and inclusive awareness. This paper aims to discuss the concept of conscientization from Paulo Freire which emphasizes the presence of consistency and inclusiveness as the fruit of full self-awareness to solve the problem of the decrease of the quality of the coastal environment and the reduce of Indonesia's coastal areas. The research approach used is qualitative and Participatory Rural Appraisal (PRA). PRA is used to map the problems and potentials of coastal communities and children's groups, including the local wisdom values of the community. The data collection technique uses interviews, observation, documentation, and group discussions from August to November 2021. Through a socio-cultural approach, and collaboration with formal and informal educational institutions, the result of this study can be a repressive and preventive model in alleviating environmental problems, especially coastal problems. By formulating and applying the Paulo Freire consientizacio model based on local potential, it was found that the reconstruction of mangrove conservation education was able to build children's critical and transformative awareness that would be able to solve problems in coastal areas. Based on an inclusive mangrove literacy approach, the application of education is targeted at the children of this generation as conservation agents capable of caring for and innovating to improve the environment with awareness that has been formed through mangrove literacy education from an early age.